(untitled) (Beacon: International Journal of Education and Social Studies, 2025)
This study examines the function of schools in promoting psychological resilience among secondary school learners during crisis conditions. A mixed-methods design was employed, integrating quantitative data collected through standardized questionnaires and qualitative data obtained from semi-structured interviews. The findings indicate a significant negative correlation between psychological resilience and perceived stress, suggesting that students with higher resilience levels experience lower stress. Participation in school-based intervention programs was identified as a significant predictor of resilience. Qualitative results revealed that schools enhance resilience through three key mechanisms: developing coping skills and psychological knowledge, strengthening peer and school-based social support systems, and providing structured environments that foster emotional stability during crises. However, challenges such as limited resources, inconsistent student engagement, and implementation barriers were also identified. Overall, the study concludes that schools play a crucial role not only as educational institutions but also as protective environments that foster psychological resilience among adolescents during crisis situations.